Homœopathic treatment of filariasis - Subramanyam, V.R.; Mishra, N.; Rai, Y.; Rakshit, G.; Pattnaik, N.M. (British Homeopathic Journal, 1990)
A single-blind study was conducted to assess the effect of homœopathic treatment on cases of bancroftian filariasis. Based on the predominant symptom, the filariasis cases were grouped as adenitis, genitalia involvement, lymphoedema and mastitis. Effect of treatment with homœopathic drugs were assessed by comparing with groups treated with placebo. Filiariasis cases treated with homœopathic medicines showed a better improved/not improved ratio (2.0) compared with cases treated with placebo (0.46). The results indicate that the improvements derived from homœopathic medicines are statistically highly significant (p<0.001).
Keywords: Bancroftian filariasis; Homœopathy